Public food procurement for sustainable food systems and healthy diets – Volume 1 - Swensson, Luana; Hunter, Danny; Schneider, Sergio; Tartanac, Florence (Food and Agriculture Organization of the United Nations, 2021)
Sustainable Public Food Procurement (PFP) represents a key game changer for food systems transformation. It can influence both food consumption and food production patterns. It can deliver multiple social, economic and environmental benefits towards sustainable food systems for healthy diets.